BindingDB Entry 50046191: Cloning, characterization and anion inhibition studies of a new¿-carbonic anhydrase from the Antarctic bacterium Pseudoalteromonas haloplanktis. - BindingDB (BindingDB, 2016)
Small molecule binding data for protein Carbonic anhydrase, Carbonic anhydrase 2, and Gamma-carbonic anhydrase, Uniprot P00915, P00918, and P40881